Energy conservation challenges and potential in Russia’s North-East region - Semenov A.S.; Bebikhov Yu.V.; Pavlova S.N.; Yakushev I.A.; Fedorov O.V.; Vladimirov O.V. (E3S Web of Conferences, 2020)
The paper discusses challenges and a potential of fuel and energy savings in one of the republics of the North-Eastern region of the Russian Federation. The authors show the challenges of energyand heatsaving, with due account too particular features of Sakha Republic (Yakutia), which include: inconsistency of the actual operating conditions of the equipment with the requirements of regulatory documents in force; problems in supplying the consumers in the decentralized zone. The region’s goals in the segment of energy saving are determined. A detailed assessment of energy-saving potential in the electricity, thermal and fuel saving sectors is carried out. Energy saving is achieved mainly by reducing the losses in general-purpose utility networks, when switching to energy-saving lighting devices, as well as by reducing electricity consumption rate for water pumping, supply and sewage disposal. Heat energy savings can primarily be achieved only by reducing losses in heating services’ networks. Considerable fuel savings can be obtained by reducing the fuel consumption rate in boiler houses and diesel-run power plants. The results show high potential for energy savings in the region. Energyand fuel-intensive activities alone could save the estimated 1 million TOE every year.